Perception of parental practices and experience of Positive emotions in adolescents (Revista de Psicología, 2019)
This research aimed to study, by ex post facto design, how parenting practices perceived by the adolescents have an influence on their ability to experience positive emotions. The sample consisted of 210 Argentinean adolescents of both sexes, age range from 14 to 16 years old. The participants completed the Positive Emotions Questionnaire (Schmidt, 2008) and the short version of an Argentinean adaptation of the Children’s Report of Parental Behavior Inventory (Richaud de Minzi, 2005). The results suggested that maternal pathological control and extreme autonomyhinders the experience of some positive emotions in children. Regarding to the paternal practices, it was found that the combination of pathological control, low acceptance and granted extreme autonomy make difficult the positive emotional experience of children.
Keywords: Parenting; positive emotionality; adolescence